2016
DOI: 10.3109/02699206.2015.1135477
|View full text |Cite
|
Sign up to set email alerts
|

Multiple phonetically trained-listener comparisons of speech before and after articulatory intervention in two children with repaired submucous cleft palate

Abstract: In Cleft Palate (CP) assessments based on phonetic transcription are the "gold standard" therapy outcome measure, despite reliability difficulties. Here we propose a novel perceptual evaluation, applied to ultrasound-visual biofeedback (U-VBF) therapy and therapy using visual articulatory models (VAMs) for two children with repaired submucous CP.Three comparisons were made: post VAM, post U-VBF and overall pre-and post-therapy. Twentytwo phonetically-trained listeners were asked to determine whether pre-or pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…A third blind-SLP was in charge of the reassessment of the 10 patients based on the audio records, so that the inter-rater reliability could be evaluated. The results show various degrees of agreement between the two raters, consistent with the findings of Roxburgh et al (2016) who reported a statistically weak agreement between the scores of 22 phonetically-trained listeners for the same patients.…”
Section: Discussion Conclusion and Perspectivessupporting
confidence: 88%
See 2 more Smart Citations
“…A third blind-SLP was in charge of the reassessment of the 10 patients based on the audio records, so that the inter-rater reliability could be evaluated. The results show various degrees of agreement between the two raters, consistent with the findings of Roxburgh et al (2016) who reported a statistically weak agreement between the scores of 22 phonetically-trained listeners for the same patients.…”
Section: Discussion Conclusion and Perspectivessupporting
confidence: 88%
“…More than three decades ago, Shawker & Sonies (1985) suggested to use ultrasound images of the tongue for the rehabilitation of English /ɹ/ for a nine year old patient. Since this first case study, English /ɹ/ rehabilitation with ultrasound remains a widely studied topic (Adler-Bock, Bernhardt, Gick et al (2003) or Gallagher (2013)), Down syndrome (Fawcett, Bacsfalvi et al (2008)), cleft palate (Roxburgh, Cleland et al (2016)), acquired apraxia of speech post stroke (Jonathan L Preston & Leaman (2014), Acher, Fabre et al (2016) and Haldin, Acher et al (2017)) or partial glossectomy (Blyth, McCabe et al (2016)).…”
Section: Articulatory Visual Illustration and Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…), repaired submucous cleft palate (e.g., Roxburgh et al . ), or Down syndrome (e.g., Fawcett et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…, Roxburgh et al . ), but diversity in study design and quality, varied responses to intervention, and low participant numbers hamper interpretation of these studies. Unfortunately, no large randomised‐controlled trials comparing approaches met the inclusion criteria for this systematic review.…”
Section: Discussionmentioning
confidence: 99%